2007
DOI: 10.4315/0362-028x-70.1.151
|View full text |Cite
|
Sign up to set email alerts
|

Natural Occurrence of Fusarium Species, Fumonisin Production by Toxigenic Strains, and Concentrations of Fumonisins B1 and B2 in Conventional and Organic Maize Grown in Spain

Abstract: Sixty samples of corn from both conventional and organic farms were tested for internal fungal contamination. Molds were identified to genus, and those belonging to the genus Fusarium were identified to species. Twenty isolates of Fusarium verticillioides were tested with a high-performance liquid chromatography-naphthalene dicarboxaldehyde-fluorescence method for their ability to produce fumonisins B1 and B2. The internal fungal infection in organic maize (63.20%) was significantly higher than that in convent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
26
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(33 citation statements)
references
References 16 publications
7
26
0
Order By: Relevance
“…F. verticillioides IV B011 strain was able to produce relatively high amounts of toxins . A similar trend was also observed by Arino et al (2007), Brown et al (2012) and Butchko et al (2012). The highest concentration of fusarin C (0.7 mg L −1 ) was produced by the strain of F. verticillioides III K048.…”
Section: Toxin-producing Ability By Fungal Strainssupporting
confidence: 82%
See 1 more Smart Citation
“…F. verticillioides IV B011 strain was able to produce relatively high amounts of toxins . A similar trend was also observed by Arino et al (2007), Brown et al (2012) and Butchko et al (2012). The highest concentration of fusarin C (0.7 mg L −1 ) was produced by the strain of F. verticillioides III K048.…”
Section: Toxin-producing Ability By Fungal Strainssupporting
confidence: 82%
“…Recently, a new species of Fusarium temperatum, morphologically similar and phylogenetically close to Fusarium subglutinans was isolated from maize in Belgium (Scauflaire et al 2011). Over the past years, it was demonstrated that Fusarium species can produce mycotoxins such as fusarin C, fusaric acid, fumonisins B 1 (FB 1 ), FB 2 and FB 3 (Porter et al 1995;Cantalejo et al 1999;Song et al 2004;Arino et al 2007). Figure 1 presents the chemical structures of these mycotoxins which exhibit various toxic effects to plants and animals and may pose a potential health risk for humans.…”
Section: Introductionmentioning
confidence: 99%
“…The natural occurrence of FBs in corn resulted from the wide distribution and the endophytic nature of Fusarium verticillioides in corn. Later, surveys were carried out to determine the levels of (Arino et al 2007;Silva et al 2007;Cano-Sancho et al 2012) and Argentina (Broggi et al 2007). Corn is considered the most important source of FBs in the human diet, and, for this reason, several countries have introduced specific regulations for the maximum content of FBs in cereals.…”
Section: Please Scroll Down For Articlementioning
confidence: 99%
“…Recent surveys have raised concerns about the extent of FB 1 contamination and its implication for food safety [6,7]. Studies published in 2007, showed that in Portugal fumonisins were found in 22% of cereals samples at concentrations between 113 and 2026 ppb [8] while in Spain up to 13.3% of the conventional corn samples contained fumonisins B 1 and B 2 at mean concentrations of 43 and 22 ppb [9]. For human exposure, the potential danger is mostly but not exclusively from homegrown corn in underdeveloped countries as Iran [10 -12].…”
Section: Introductionmentioning
confidence: 99%